Comparison of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in patients diagnosed with trigeminal neuralgia and healthy controls (Annals of Medical Research, 2021)
Aim: Trigeminal neuralgia (TN) is a common cranial nerve disease, but its pathogenesis has not yet been fully elucidated. The neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) have been investigated in recent years as markers of systemic inflammation, and their determination presents as a lower-cost, more practical, and simpler method compared to other inflammation markers. This study aimed to evaluate the possible role of systemic inflammation in TN etiopathogenesis based on NLR and PLR values.Materials and Methods: The study included 55 male and female patients aged 18 to 60 years, who were diagnosed with TN at the Neurology Clinic of our university according to the criteria of Headache Classification Committee of the International Headache Society 2018 (Cephalalgia2018), and 48 healthy controls. Demographic and clinical variables, such as age and gender were retrospectively obtained from medical records.Results: In terms of sociodemographic data, both groups had similar characteristics. The NLR values were 1.84±0.81 for the patient group and 1.92±0.79 for the control group. There was no statistically significant difference in NLR between the two groups (p = 0.447). The PLR values were 101.91±30.24 and 97.84±30.24 for the patient and control groups, respectively, indicating no statistically significant difference (p = 0.439). Conclusions: The role of systemic inflammation in TN pathophysiology remains controversial. It is considered that an inflammatory process may occur in the pathophysiology of TN, but this is characterized by local neurogenic inflammation rather than the effect of a systemic inflammatory response.
Keywords: Cranial nerve; headache; inflammation; neutrophil-lymphocyte ratio; platelet-lymphocyte ratio; trigeminal neuralgia